2022
DOI: 10.1111/are.15893
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of multiple bacterial infections in Pacific whiteleg shrimp, Litopenaeus vannamei

Abstract: A rare incidence of multiple bacterial infections was reported in Litopenaeus vannamei grow‐out ponds in India. The pathogenic organisms identified are Aeromonas veronii, Bacillus flexus, Kurthia gibsonii, Shewanella decolorationis, Bacillus cereus and Shewanella amazonensis. The infected shrimp showed various clinical and morphological changes such as mucus secretion in the hepatopancreas, bacterial spots in the carapace, red or pink discoloration of abdomen with black stripes and highly melanized body. The H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Both IMNV and WSSV don’t have the same tropism and they are highly virulent. Dewangan et al (2022) reported multiple bacterial infections to be highly pathogenic in L. vannamei grow-out ponds in India. On the other hand, Flegel et al (2004) showed that grossly normal shrimp were concurrent hosts to several viruses, and that some had significant negative correlations with shrimp size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both IMNV and WSSV don’t have the same tropism and they are highly virulent. Dewangan et al (2022) reported multiple bacterial infections to be highly pathogenic in L. vannamei grow-out ponds in India. On the other hand, Flegel et al (2004) showed that grossly normal shrimp were concurrent hosts to several viruses, and that some had significant negative correlations with shrimp size.…”
Section: Discussionmentioning
confidence: 99%
“…reported the presence of IMNV and WSSV in Brazil. Both IMNV and WSSV don't have the same tropism and they are highly virulent Dewangan et al (2022). reported multiple bacterial infections to be highly pathogenic in L. vannamei grow-out ponds in India.…”
mentioning
confidence: 99%
“…Escherichia coli [30] and Aeromonas hydrophila are among the causes of bacterial shrimp enteritis, which can lead to slow growth, significant body weight loss, and even death in severe cases. Aeromonas veronii has also been identified as a pathogen that is commonly isolated from infected and dead shrimp [31].…”
Section: Acquisition Of Raman Spectrum Datamentioning
confidence: 99%
“…reported the presence of IMNV and WSSV in Brazil. Both IMNV and WSSV do not have the same tropism, and they are highly virulent Dewangan et al (2022). reported multiple bacterial infections to be highly pathogenic in L. vannamei grow-out ponds in India.…”
mentioning
confidence: 99%